Peace, sweet peace: ants become less aggressive when carbohydrates abound. (2nd October 2020) - Chinarelli, Henrique D.; Pupe, Ana E.; Leal, Laura C.
Abstract : 1. An animal's energetic condition is causally related to its ability to display costly behaviours such as aggressive behaviours. Aggressive behaviours are used by animals interacting with heterospecifics when competing through interference. Therefore, how does the abundance of energetic resources influence the pattern of interspecific competition by interference at the community level? To answer this, ants were used as models because the aggressiveness of workers is fuelled by the consumption of carbohydrates. 2. It was hypothesised that ant species are more aggressive when carbohydrates were more abundant. Consequently, the strength of competition by interference would increase, changing the patterns of ant species' resource use at the community level. 3. This study experimentally increased the availability of carbohydrates and counted the number of aggressive behaviours, the probability of ant species exclusion, and the composition of ant morphospecies exploring protein baits before and after the addition of carbohydrates. 4. After the addition of carbohydrates, ants displayed 42% less aggressive behaviour and were twice as prone to exclude other ant species from the protein baits. This led to changes in the composition of ants exploring the protein baits before and after carbohydrate addition. 5. In general, ants became less motivated to engage in competitive interactions when carbohydrates were more available. However, this response was not homogeneous as the occurrence and aggressiveness of some species, such as the nectarivores, were higher when carbohydrates abound. As carbohydrates are mainly offered by plants, this study's results suggest that plants can indirectly shape the structure of ant communities through ant responses to the availability of carbohydrates. Abstract : Ants become less aggressive while competing for food resources when we experimentally added carbohydrate sources in the habitat. Experimental addition of carbohydrates also reduced ant motivation in fighting against other ant species for food resources. Addition of carbohydrates had a larger impact on the aggressiveness and foraging strategies of nectarivore species than for ants belonging to other foraging guilds.